A fluorescent glyconanoprobe based on quantum dots and thiolated glucose: Applications in monolayers and spheroids of cancer cells - Henrique, Rafaella B.L.; Santos, Ana L.F.; Pereira, Maria I.A.; Oliveira, Weslley F.; Santos, Beate S.; Pereira, Goreti; Fontes, Adriana; Cabral Filho, Paulo E. (Biochimica et biophysica acta. General subjects, 2023)
The differential energy metabolism of cancer cells has stimulated the development of tools that can be applied to better understand the complex biological interaction involved in the uptake of glucose analogs at the cellular level in this disease. Herein, we explored the outstanding optical properties of quantum dots (QDs) to develop a new fluorescent glyconanoprobe using the 1-thio-β-d-glucose (Glc). Then, monolayers and spheroids of HeLa cells were applied to probe the biological interaction with the conjugate through fluorescence techniques. Spheroids have been gaining prominence for better mimicking the tumor microenvironment. The Glc-QDs conjugate was prepared by a facile and direct procedure based on the affinity of the Glc thiol group by the QD semiconductor surface. The conjugation was evaluated and confirmed by Zeta potential (ζ) measurements, FTIR spectroscopy, and fluorescence correlation spectroscopy (FCS). Moreover, a biological assay using Candida albicans yeasts coated with concanavalin A, by exploring the lectin-carbohydrate affinity, was also developed to further confirm the conjugation, which corroborated the previous analyses. The hanging drop method was used to prepare the spheroids. The fluorescence microscopy analyses indicated an intracellular labeling by the glyconanoprobe, in both cell culture models. Flow cytometry assays revealed effective uptake of the conjugate (above ca. 76%), even by cells cultivated as spheroids, applying short incubation time. Therefore, a new fluorescent glyconanoprobe was developed, which showed potential to be applied for investigating mechanisms involved in the uptake of glucose analogs, both by simpler and complex cancer biological models, as monolayers and spheroids.The differential energy metabolism of cancer cells has stimulated the development of tools that can be applied to better understand the complex biological interaction involved in the uptake of glucose analogs at the cellular level in this disease. Herein, we explored the outstanding optical properties of quantum dots (QDs) to develop a new fluorescent glyconanoprobe using the 1-thio-β-d-glucose (Glc). Then, monolayers and spheroids of HeLa cells were applied to probe the biological interaction with the conjugate through fluorescence techniques. Spheroids have been gaining prominence for better mimicking the tumor microenvironment. The Glc-QDs conjugate was prepared by a facile and direct procedure based on the affinity of the Glc thiol group by the QD semiconductor surface. The conjugation was evaluated and confirmed by Zeta potential (ζ) measurements, FTIR spectroscopy, and fluorescence correlation spectroscopy (FCS). Moreover, a biological assay using Candida albicans yeasts coated with concanavalin A, by exploring the lectin-carbohydrate affinity, was also developed to further confirm the conjugation, which corroborated the previous analyses. The hanging drop method was used to prepare the spheroids. The fluorescence microscopy analyses indicated an intracellular labeling by the glyconanoprobe, in both cell culture models. Flow cytometry assays revealed effective uptake of the conjugate (above ca. 76%), even by cells cultivated as spheroids, applying short incubation time. Therefore, a new fluorescent glyconanoprobe was developed, which showed potential to be applied for investigating mechanisms involved in the uptake of glucose analogs, both by simpler and complex cancer biological models, as monolayers and spheroids.